PENGARUH PERISTIWA GERAKAN 30 SEPTEMBER 1965 TERHADAP KONDISI SOSIAL POLITIK DI CIREBON - Rofi'i, Ahmad Faiz (Universitas Sultan Ageng Tirtayasa, 2024)
This article examines the influence of the 1965 G30S events on socio-political conditions in Cirebon. This research uses historical methods which includes heuristics, criticism, interpretation, and historiography. The results showed that the socio-political conditions in Cirebon before the G30S event were quite stable. However, after the G30S incident, the situation in Cirebon was uncontrollable, there were mass actions, and demands for the dissolution of the PKI by various youth organizations and mass organizations, one of which was Nahdlatul Ulama. NU was the most vocal in its demands because it could not be separated from the history of the old order period, which was quite tense, especially when the PKI launched unilateral actions. After the G30S, the situation in Cirebon was not as critical as in East and Central Java, where large-scale casualties occurred. However, small-scale movements occurred in several places, such as in Kapetakan, Plumbon, Astanajapura, Lemah Abang, Karang Wareng, and Waled. Preventive efforts were immediately made both at the provincial and local levels by West Java Governor H. Mashudi and Commander Ibrahim Adjie by issuing a policy prohibiting PKI activities and making rules to dismiss employees, government officials suspected of being PKI. As a result, the Mayor of Cirebon RSA. Prabowo and Cirebon District Regent E. Harun Zainal Abidin as PKI cadres were dismissed and imprisoned in 1966.